Operational Dynamic Response of Burj Khalifa and Reinforced Concrete Buildings for Safety Against Pounding - Rao, Praveena; Pollayi, Hemaraju (Applied Science and Engineering Progress, 2023)
Random ground motions in horizontal, vertical and arbitrary directions radiate away from the focus or the hypocenter under the surface of the earth during an earthquake. When the earth shakes violently, the buildings, which act as vertical cantilevers, undergo vibrations inducing significant inertial forces. Large uncertainties are associated with the response of the buildings to random lateral forces; thus it is of paramount importance to understand the dynamic structural behavior of high rise buildings. Real world high rise building such as Burj Khalifa has been analyzed by response spectrum analysis with the lumped-mass model. The response of Burj Khalifa is simulated when subjected to ground acceleration motion of different earthquake recordings within a MATLAB framework. The ground motion acceleration databases of the El Centro earthquake in 1940 and Bhuj earthquake in 2001 are taken as inputs for the present analysis with other inputs pertaining to different storey masses, storey-stiffness, number of stories, damping ratios and mode shapes. Furthermore, numerical examples to demonstrate the impact of a safe seismic gap between adjacent buildings to prevent pounding or collision during seismic events are presented. It may be observed that computation and adoption of critical gaps between buildings facilitate the best-optimized use of land and provide safety against the pounding of multi-storey buildings under the effect of earthquake excitations.